Women Participation in Sericulture Farming: An Exploration of Issues and Challenges in Kashmir. (International Journal of Food and Nutritional Sciences, 2022)
India contributes almost 18% of the world's raw silk, ranking next to China. The region of Jammu and Kashmir has been a prominent stakeholder in the industry. Sericulture is an age-old occupation and has an important role in Kashmir's economic development. Women perform 60% of sericulture's activities, making it one of their significant livelihoods that promote the empowerment of rural women. However, women's participation in this industry has declined due to several factors. Thus, the study explored the various causes of the decline in sericulture in Kashmir and the barriers that hinder women from participating in this industry.